2021
DOI: 10.1093/jn/nxaa333
|View full text |Cite
|
Sign up to set email alerts
|

Gene Set Enrichment Analysis of Selenium-Deficient and High-Selenium Rat Liver Transcript Expression and Comparison With Turkey Liver Expression

Abstract: Background Better biomarkers of selenium (Se) status and a better understanding of toxic Se biochemistry are needed to set safe dietary upper limits. In previous studies, differential expression (DE) of individual liver transcripts in rats and turkeys failed to identify a single transcript that was consistently and significantly (q < 0.05) altered by high Se. Objectives To evaluate the effect of Se status on rat liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Se exhibits antioxidant, anti-inflammatory, anticarcinogenic, potential antiviral and antibacterial activity [4]. Its biological function is achieved through the insertion of this trace element into a family of proteins known as selenoproteins [5]. Among these, glutathione peroxidase (GSH-Px) is a pivotal component of the antioxidant glutathione pathways which detoxifies lipid peroxides and provides protection of cellular and subcellular membranes against reactive oxygen species (ROS) damage [6].…”
Section: Introductionmentioning
confidence: 99%
“…Se exhibits antioxidant, anti-inflammatory, anticarcinogenic, potential antiviral and antibacterial activity [4]. Its biological function is achieved through the insertion of this trace element into a family of proteins known as selenoproteins [5]. Among these, glutathione peroxidase (GSH-Px) is a pivotal component of the antioxidant glutathione pathways which detoxifies lipid peroxides and provides protection of cellular and subcellular membranes against reactive oxygen species (ROS) damage [6].…”
Section: Introductionmentioning
confidence: 99%
“…GO and KEGG analysis showed that differentially expressed mRNAs and lncRNA target genes were mainly involved in oxidative stress, oxidative phosphorylation, endocytosis, apoptosis, metabolism, and other processes. The transcriptional expression data of the liver in rats with an Se deficiency diet indicated that Se deficiency changed some biological states or processes, including oxidative phosphorylation, ROS, xenobiotic metabolism, fatty acid metabolism, and glutathione metabolism [46]. Other studies have shown that dietary Se consistently affects inflammatory or immune pathway signaling networks in liver and lung tissue in mice [47].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, dietary supplementation of keratinase at both doses of 100,000 U/kg and 200,000 U/kg have a better redox status, indicated by higher GPX activity and lower MDA concentration, than those of the control. The better redox status in muscle by keratinase supplementation could be explained by 1) keratinase improved the digestibility of ash, which might improve the utilization of selenium; as a selenium-dependent enzyme ( Sunde, 2021 ), GPX activity could be improved by the selenium utilization ( Zhao et al, 2017 ); 2) keratinase can improve the hydrolysis of the proteins containing cysteine to release cysteine ( Gradisar et al, 2005 ; Huang et al, 2018 ), a precursor of glutathione, thus increase the body synthesis glutathione ( Dennis et al, 2019 ); 3) glutathione/GPX system plays an important role in protecting the cells against oxidative stress ( Fu et al, 2007 ; Surai, 2020 ). Taken together, these findings could help explain that dietary supplementation of keratinase improved the meat quality relative to the control.…”
Section: Disscussionmentioning
confidence: 99%